THE USE OF DEIXIS IN STUDENTS’ WRITING DESCRIPTIVE TEXTS - Mutia Olivia Indriastuti; Anni Holila Pulungan; Muhammad Natsir (Universitas Negeri Medan, 2023)
Students are able to convey their ideas, emotions, and feelings to the reader through their piece of writing. One area of pragmatics called deixis is also one of the writing aspects that students must be aware of in order provide meaning in writing. This article was aimed to found how the reason deixis used in the students’ writing descriptive text at the tenth grade MIA 2 high school Kemala Bhayangkari Medan. The data in the study is analyzed through descriptive qualitative. Three methods used include document analysis, observation, and interviews by the researcher. The result of this research showed five types of deixis, how the deixis used, and the reason deixis used in their writing using Levinson theory (1983). The results have revealed that the reason students used deixis are: to indicate a specific location, chronology events, to conveying a personal point of view, to incorporate cultural and social signifiers, and to create a strong and coherent connection. This study's results should help students learn more about how language works in real life and how words point to things. This will especially help them use the right words to improve their writing skills.